Pengaruh Gender dan Strategi Pembelajaran Terhadap Kemampuan Berpikir Kritis Matematika Siswa Sekolah Dasar - Made Sri Astika Dewi; Nyoman Ayu Putri Lestari; Ni Made Ignityas Prima Astuti; I Putu Agus Dharma Hita; Kadek Lina Kurniawati; Aditya Rhido Fatmawan; Isyarotullatifah Isyarotullatifah (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study was to reveal the influence of gender and learning strategies on the mathematical critical thinking skills of fifth grade students at SDN 4 Pendem, Jembrana District. This study uses a quantitative approach with a 2 x 3 factorial design. From the results of the critical thinking ability test, it is found that the sig value for gender is 0.40 0.05, so it can be concluded that there is no difference in the average score of mathematical critical thinking skills. students who are influenced by gender. The sig value for the learning strategy is 1.010 0.05, so it can be concluded that there is no difference in the average score of students' mathematical critical thinking skills which is influenced by the learning strategy. There is no difference in the average score of critical thinking skills between male and female students who follow the learning strategy. Based on the results of data analysis, it was concluded that there was no difference in the average mathematical critical thinking ability of students which was influenced by gender.